Marine Amateur Radio (American : MC Graw Hill, 2005)
Developed by the United States Power Squadrons, the world's largest private, nonprofit boating organization, Marine Amateur Radio is a complete guide to the use of ham radio for two-way and network communications among boats and between boats and shore stations. Briefly, succinctly, and clearly, this sturdy handbook lays out the advantages of ham radio for boaters. It explains how to get an operator's license, how to select and install a receiver and antenna, and how to use the radio for voice and Morse code communications with other boats and to shore--including inexpensive telephone patches to home. It also shows readers how to link up with marine voice nets for weather and safety communication.
From the Back Cover
ENJOY FAST, CLEAR, AFFORDABLE COMMUNICATIONS—SHIP-TO-SHIP OR SHIP-TO-SHORE
When you’re miles offshore and the nearest vessel is somewhere over the horizon, you need a fast, reliable, easy-to-operate communication system. Marine Amateur Radio provides all the information you need to select, install, and operate an inexpensive and completely dependable ham radio system on any boat, power or sail. This well-illustrated guide succinctly explains how ham radio gives you the advantages of a single-sideband system at a fraction of the cost. You’ll learn how to use your radio for voice or Morse code communications, check and send e-mail, link up with on-shore signal repeaters to extend your range, and even make personal phone calls using your ham radio. Designed to lie flat for easy use onboard, this compact manual shows you how to
Obtain a Technician Class or General Class operator’s license
Use ham radio for coastal, high-seas, or worldwide communications
Tune the optimal frequency band for the time of day and range of transmission
Keywords: Marinne radio stations - Amateurs manuals; Radio - Installation on ships - Amateurs manuals; Amateur radio stations